Supportive social interaction as a concept for describing the situation of persons experiencing an infertility crisis - Malina, Alicja (Przegląd Psychologiczny, 2023)
Objective: This article presents the definitions and justification of the necessity to introduce the original concept of supportive social interaction into scholarly discourse. Supportive social interaction is understood as a group interaction encompassing speaking or listening in an informal and judgement-free environment, which is connected with the necessity – and also provides an opportunity – to reciprocally disclose the experiences, needs and personal convictions of the persons participating in the said interaction and leads to a reduction of stress. The differences between traditional approaches to support and supportive social interactions and their significance in the treatment of infertility have been outlined in this article. Theses: Supportive social interactions, a precondition of which is the occurrence of disclosure, vary in terms of quality and function from support in the traditional sense of the word. They are also a source of stress reduction in the process of treating infertility using assisted reproductive technologies. Conclusion: Supportive social interactions are increasingly important in the context of infertility treatment. The proposed concept is an essential element describing the functioning of persons experiencing an infertility crisis.